Concept and application of ḍamān in Islamic commercial law - Jaffar, Zainudin (The University of Edinburgh, 1994)
This study deals with an important concept in fiqh known as ḍamān. Despite its universal usage in various areas of law, including that of criminal law and law of torts especially in facilitating award of compensation, this study will confine its survey within the bounds of commercial transactions. Ḍamān forms one of the most complicated subject-matters in the Islamic Law of Obligation. In this context, ḍamān is generally perceived as civil liability in the widest meaning, arising from the non-performance of contractual obligation, violation of trust, misrepresentation and unlawful enrichment. Firstly, this study will discuss suretyship, as ḍamān is, to some extent, treated as synonymous with kafālah by the jurists. Secondly, ḍamān will be surveyed as a method of redress of any contractual irregularities under the notion of gharāmah. Such practices are motivated by the Sharī'ah doctrines of maqāṣid shar'iyyah (objectives of the law), upholding the concept of lā ḍarara wa lā ḍirār (no harm shall be inflicted or reciprocated) and respecting the notion of sanctity of legitimate ownership (ḥurmat al-milkiyyah) and freedom of contract (ḥurriyat al-ta'āqud). Methods of establishing liability (ṭuruq ithbāt al-ḍamān) and its waivers (al-i'fā') min al-ḍamān), provision of redress (mabda' al-ta'wīḍ) and the institutional framework which are involved in it are then discussed. The study will be concerned with the prescriptions of the Qur'ān and Sunnah on ḍamān and their explanations in the classical manuals of Islamic Law. In addition, certain post-classical texts offering specific treatment of ḍamān, particularly al-Baghdādī's Majma' al-Ḍamānāt and al-Ma'danī's Taḍmln al-Ṣunnā' will be studied. Also, decisions by juristconsults of various localities, recorded in various collections of fatāwā and court decisions in the literature of adab al-qaḍā, will be examined to enhance our knowledge of the way ḍamān has been treated. For the purpose of systemization, texts of Uṣūl al-Fiqh and Qawā'id Fiqhiyyah are essential. Similarly, evidence on the economic history of Muslim civilization in the form of actual contracts, letters, business records and institutional operations, are examined. The research also relies heavily on the codifications of Islamic law like the Ottoman Majallat al-Aḥkām al-'Adliyyah, Qadrī Bāshā's Murshid al-Ḥayrān and the Ḥanbalīs Majallat al-Aḥkām al-Shar'iyyah. Finally, an analysis of the contemporary legislations in Egypt, the United Arab Emirates and Malaysia will prove that a classical concept like ḍamān is still vital for modem commerce. This also lays stress on the importance of neo-ijtihād to ensure ability and competence to apply ḍamān to fresh problems in commercial life.
Keywords: Ḍamān; Islamic law